Application of Bio-Electrical Instruments for Monitoring the Effect of Muscle Massage on Post-Stroke Patients Through Electromyography Signal Measurement - Triwiyanto Triwiyanto; Torib Hamzah; Sari Luthfiyah; Bedjo Utomo; Urip Mudjiono (Frontiers in Community Service and Empowerment, 2022)
The problems faced by partners are: in carrying out traditional massage massage practice activities, partners do not carry out the process of recording medical conditions before or after the massage process. Thus, this causes partners to be unable to remember the conditions before and after the provision of traditional massage therapy. In addition, when giving traditional massage to patients who have to return periodically, partners cannot know the impact after giving traditional massage. So, to know the result is to ask questions to the patient (e.g. "how is the result after the massage?"). Therefore, monitoring the massage process in post-stroke patients is qualitative and subjective. The implementation methods are: Measuring the physical and medical parameters of the patient such as weight, height and blood pressure, before and after the partner performs traditional massage to the patient, the bio-electrical muscle signal (EMG) is measured by attaching electrodes to the partially paralyzed limbs. Next, the patient contracted the muscle by pressing a rubber ball connected to an electronic pressure measuring module. Together with partners, they monitor the measured value of the muscle bio-electric signal (which is displayed on the computer panel), c) monitor the bio-electric signal in post-stroke patients who undergo traditional massage therapy in subsequent therapy activities (2-5 therapies). The output of PKM activities with the title "Implementation of Muscle Bio-electric Signal Measurement to Monitor the Healing Process of Post-Stroke Patients as an Effort to Support Traditional Massage Workers" is the device that can be used by the partners to monitor the effect of the massage to the patient. The targets and achievements expected in this PKM activity are that partners can monitor the effectiveness of traditional massage with the support of science and technology.